Tissue Doppler E′ to detect diastolic dysfunction from quantitative echo: a Z-score of E′ preferable to raw E′ velocities. (22nd September 2015) - Yadav, H; Unsworth, B; Medlow, K; Baruah, R; Wasan, B; Mayet, J; Francis, DP
Abstract : Introduction: Despite their potential as a sensitive measure of ventricular performance, tissue Doppler velocities vary with normal ageing. This is inconvenient for non-specialists to interpret, and makes it difficult to use as an entry criterion for clinical studies. Age-adjusted tissue Doppler Z-scores may avoid these disadvantages and be more discriminant for myocardial impairment than raw velocities. Methods: We conducted a metaregression of studies reporting age-specific normal tissue Doppler velocities to determine a consensus formula for Z-scores (nine studies, 1990 patients), which we then tested in an independent study at our institution. We then compared Z-scores head-to-head with raw velocities in their ability to distinguish a fresh set of 81 healthy subjects from groups in whom subtle ventricular dysfunction may be expected: 50 patients with dilated cardiomyopathy, 50 with aortic regurgitation and 50 with mitral regurgitation. Results: Discriminant capacity, assessed by the area under the receiver operator characteristic curves, was higher for Z-scores than for raw velocities in each patient group. At the septal angle of the mitral annulus: dilated cardiomyopathy (DCM) 0.95 versus 0.92 (p = 0.03), aortic regurgitation (AR) 0.83 versus 0.78 (p = 0.02), mitral regurgitation (MR) 0.85 versus 0.81 (p = 0.04). At the lateral angle: DCM 0.94 versus 0.88 (p = 0.005), AR 0.92 versus 0.83 (p = 0.001), MR 0.87 versus 0.85 (p = 0.31). Conclusion: Z-scores of tissue Doppler velocities are better able than raw velocities to detect myocardial impairment in valve or heart muscle disease. Calculation needs only raw velocity and age. Tissue Doppler Z-scores might be used to create a new, sensitive, definition of ventricular dysfunction, and may make it easier for non-specialists to interpret reports.